Application of the destination multiculturality in tourism promotion on the example of Vojvodina - Ćuruvija Ivana; Ćuruvija Miloš; Pavlović Nataša (Trendovi u Poslovanju)
It is a well-known fact that the culture of a region is one of the basic resources which acts as an attractive factor in tourism. In some destinations many different ethnic communities live together which creates a specific culture of a region in the sense of its multiculturality, and this element could be very important in tourist destination promotion. Many multiethnic cities and regions in the world use this element in tourism in many ways, from organizing events to promotion of specific ethnical gastronomy. Vojvodina is a region in which multiculturality is very expressed, as there are over 25 nationalities living together in peace and harmony for many years. In this paper, Vojvodina is taken as an example used to investigate the use of multicultural elements in tourism promotion. The paper is based on the research of attitudes of tourism workers from Vojvodina region about the use of multiculturality in tourism promotion, based on which conclusions are given about the possible use of this interesting and important Vojvodina's element in future promotional activities.